Most blessed of the patriarchs eaudiobook - Gordon-Reed, Annette (Recorded Books Inc., 2016)
A groundbreaking work of history that explicates Thomas Jefferson's vision of himself, the American Revolution, Christianity, slavery, and race. Thomas Jefferson is still presented today as a hopelessly enigmatic figure, despite being written about more than any other Founding Father. Lauded as the most articulate voice of American freedom, even as he held people in bondage, Jefferson is variably described by current-day observers as a hypocrite, an atheist, and a simple-minded proponent of limited government. Now, Pulitzer Prize-winning historian Annette Gordon-Reed teams up with the country's leading Jefferson scholar, Peter S. Onuf, to present an absorbing and revealing character study that finally clarifies the philosophy of Thomas Jefferson. Tracing Jefferson's development and maturation from his youth to his old age, the authors explore what they call the "empire" of Jefferson's imagination-his expansive state of mind born of the intellectual influences and life experiences that led him into public life as a modern avatar of the enlightenment, who often likened himself to an ancient figure-"the most blessed of the patriarchs."